ChemInform Abstract: Enantioselective Radical Alkynylation of C(sp3)—H Bonds Using Sulfoximine as a Traceless Chiral Auxiliary. Issue 48 (December 2015) - Nagatomo, Masanori; Yoshioka, Shun; Inoue, Masayuki
Abstract: The title reaction is achieved using only a chiral sulfoximine (II) and benzophenone under photo‐irradiation.